1995
DOI: 10.1002/pd.1970150410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of maternal serum dimeric inhibin a as a first‐trimester marker of down's syndrome

Abstract: While second-trimester prenatal screening programmes for Down's syndrome have become established in prenatal care, it would be advantageous to be able to offer screening in earlier pregnancy. To this end, we have evaluated a new potential maternal serum marker, dimeric inhibin A, as a possible first-trimester marker. Dimeric inhibin A was measured in prospectively collected maternal serum from 23 cases of Down's syndrome and matched chromosomally normal controls, at 11-13 weeks' gestation. Levels of this prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…The recent development of sensitive and highly specific ELISAs for inhibin A [2], inhibin B [1], inhibin pro-aC [3], and activin A [4] and their subsequent application have permitted important insights to be gained into normal [5][6][7] and abnormal pregnancies [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of sensitive and highly specific ELISAs for inhibin A [2], inhibin B [1], inhibin pro-aC [3], and activin A [4] and their subsequent application have permitted important insights to be gained into normal [5][6][7] and abnormal pregnancies [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Dimeric inhibin A has been reported to meet these criteria. [4][5][6][7][8][9][10][11] Inhibins are circulating dimeric glycoprotein hormones synthesised by the gonads and the placenta. The subunit can combine with one of two subunits ( A and B) to form inhibin A or inhibin B. Inhibin precursors are also present in maternal circulation.…”
mentioning
confidence: 99%
“…Further studies using a new assay specific for dimeric inhibin A ( ab A) have suggested a possible role for dimeric inhibin A as a screening marker, since elevated serum levels have been found in women with fetuses affected by Down's syndrome in both the first and the second trimesters. 28,29 In this study, we extended the investigation of inhibin A to a larger group of women with fetuses affected by Down's syndrome or trisomy 18 and compared its performance in screening with that of the established markers alpha-fetoprotein, intact human chorionic gonadotropin, and the b subunit of human chorionic gonadotropin.…”
mentioning
confidence: 99%